The Effect of the Project-Based Learning (PjBL) Model on Students’ Analytical Thinking Skills - M. Amris Parwandi; Septiana Dwi Utami; Titi Laily Hajiriah (Lombok Institute, 2026)
Analytical thinking is a higher-order thinking skill required for understanding complex biological concepts, including the nervous system. This study aimed to examine the effect of Project-Based Learning (PjBL) on students’ analytical thinking skills. A quantitative approach was employed using a quasi-experimental method with a nonequivalent control group design. The sample was selected through purposive sampling and comprised 61 eleventh-grade students at SMAN 1 Gunungsari, including 30 students from class XI F as the experimental group and 31 students from class XI D as the control group. Data were collected using essay tests based on five indicators of analytical thinking skills, observation sheets, and documentation. The data were analyzed using the Shapiro–Wilk test to assess normality, Levene’s test to assess homogeneity of variance, the Mann–Whitney U test to examine differences between groups, and normalized gain (N-gain) analysis to determine the level of improvement. The mean score of the experimental group increased from 52.8 to 73.6, whereas that of the control group increased from 50.6 to 61.9. The Mann–Whitney U test yielded U = 64.500, Z = −5.925, and p < 0.001, indicating a significant difference between the two groups. The experimental group achieved an N-gain of 0.44, categorized as moderate, whereas the control group obtained an N-gain of 0.23, categorized as low. These findings indicate that PjBL resulted in significantly higher analytical thinking skills and greater improvement than conventional instruction in learning the nervous system.